Technology Of Using Integrated Skills in EFL Classes - Bakhieva Mekhriban Tleobergen kizi (Scientific Trends, 2024)
The article deals with the integration of multiple language skills in English as a Foreign Language (EFL) instruction has emerged as an effective pedagogical approach for enhancing learners' overall proficiency. This paper describes the technology of using integrated skills in EFL classes, focusing on the synergistic teaching of listening, speaking, reading, and writing to create a holistic learning environment. By employing innovative teaching tools and strategies, the study aims to foster an immersive learning experience that mirrors real-world communication. The paper highlights the theoretical underpinnings of skill integration, practical applications in the classroom, and the impact of this approach on learners' language competence.
Keywords: Integrated skills, EFL, classes, technology, learning environment, learning tools.